경제성 관점에서 문화기술연구원설립에 대한 정책적 제언 -조직구조, 규모 및 설립시기를 중심으로 - 이용규; 주혜성; Lee, Yong-Kyu; Ju, Hye-Seong (한국콘텐츠학회 논문지, 11(10), 2011)
The establishment of Culture Technology Institute is now under discussion. In case of advanced countries (including USA, Japan and EU) practices market-oriented policies in the area of culture and entertainment industry. Therefore it is hard to find out Government-funded Institute which Korea could benchmark. In this situation, there are many different opinions about its organizational structure, size of organization and budget, and when the institute should be established. This study proposed a Consolidated-Decentralized model as a proper organizational structure after evaluating 4 different models based on 4 criterion. And based on results produced by the model developed for our research, this study suggested proposals that the number of research personnel and the size of budget should be larger than 300 persons and 1200 billion won respectively. However, the establishment of institute should be decided by not only economic factor but also various factors such as political element, externality, private company investment and effect on production inducement etc. If new institute focused on different area from ETRI, then the time and size of the institute could be decided by the result of policy analysis. 문화기술연구원(이하 CT연구원)의 설립이 현재 논의 중에 있다. 외국의 경우에는 CT 분야는 민간부분이 시장을 주도하는 모델을 지향하고 있다. 따라서 우리나라가 벤치마킹할 수 있는 정부출연형태의 연구기관을 해외에서 찾아보기 어렵다. 이러한 상황에서 CT연구원의 조직구조, 규모 및 설립시기에 대하여 다양한 주장이 제기되고 있다. 본 연구는 CT연구원을 신설할 것인가 혹은 기존 연구조직을 흡수할 것인가와 연구 조직을 통합 분산하는 것을 기준으로 4가지 유형으로 구분하였다. 그리고 4가지의 기준을 적용하여 이들을 평가하여 흡수-분산형을 바람직한 조직구조로 제시하였다. 또한, 독립적인 연구원으로 전환하여 얻을 수 있는 편익을 측정하기 위하여 시뮬레이션 모형을 개발하고, 여기에서 도출된 결과를 토대로 CT연구원은 예산은 최소 1200억 원 그리고 연구원의 인원은 최소 300명이 되어야 경제적 실익이 발생하는 것으로 추정하였다. 하지만, CT연구원의 설립여부는 경제성 분석의 결과 이외에 정책성 요인, 생산유발효과, 외부성, 민간투자유치규모 등 여러 요인들을 토대로 최종 결정하여야 한다. 또한, 신설될 CT연구원이 기존 정부출연 연구기관과는 다른 연구영역을 담당할 경우에는 정책적인 판단에 의해 설립 규모와 시기를 결정할 수 있을 것으로 판단하였다.